Neural Network Approximation of Helicopter Turboshaft Engine Parameters for Improved Efficiency - Vladov, S. I.; Владов, С. І.; Yakovliev, R. P.; Яковлев, Р. П.; Bulakh, M.; Vysotska, V.; Serhii Vladov (Energies. – 2024. – Vol. 17, Issue 9. – Article 2233, 2024)
Робота присвячена розробці методу нейромережевої апроксимації параметрів турбовального двигуна вертольота, який є основою для дослідження енергетичних характеристик двигуна з метою підвищення ефективності, надійності та безпеки польотів. Для навчання пропонується використовувати тришарову нейронну мережу прямого розповсюдження з лінійними нейронами у вихідному шарі, в якій алгоритм масштабного спряженого градієнта модифікується шляхом введення моментного коефіцієнта в аналітичний вираз.

The work is devoted to the development of a method for neural network approximation of helicopter turboshaft engine parameters, which is the basis for researching engine energy characteristics to improve efficiency, reliability, and flight safety. It is proposed to use a three-layer direct propagation neural network with linear neurons in the output layer for training in which the scale conjugate gradient algorithm is modified by introducing a moment coefficient into the analytical expression. This modification helps in calculating new model parameters to avoid falling into a local minimum. The dependence of the energy released during helicopter turboshaft engine compressor rotation on the gas-generator rotor r.p.m. was obtained. This enables the determination of the optimal gas-generator rotor r.p.m. region for a specific type of helicopter turboshaft engine. The optimal ratio of energy consumption and compressor operating efficiency is achieved, thereby ensuring helicopter turboshaft engines’ optimal performance and reliability. Experimental data support the high efficiency of using a three-layer feed-forward neural network with linear neurons in the output layer, trained using a modified scale conjugate gradient algorithm, for approximating parameters of helicopter turboshaft engines compared to the analogues. Specifically, this method better predicts the relations between the energy release during compressor rotation and gas-generator rotor r.p.m. The efficiency coefficient of the proposed method was 0.994, which exceeded that of the closest analogue (0.914) by 1.09 times.

Работа посвящена разработке метода нейросетевой аппроксимации параметров вертолетного турбовального двигателя, являющегося основой для исследования энергетических характеристик двигателя с целью повышения эффективности, надежности и безопасности полетов. Для обучения предлагается использовать трехслойную нейронную сеть прямого распространения с линейными нейронами в выходном слое, в которой алгоритм масштабно-сопряженного градиента модифицирован путем введения в аналитическое выражение моментного коэффициента.
Keywords: Україна; publikatsii u WoS; neural network approximation; helicopter turboshaft engines; energy; power; efficiency; training; gas-generator rotor r.p.m.; scaled conjugate gradient algorithm; нейромережева апроксимація; вертолітні турбовальні двигуни; енергія; потужність; ефективність; навчання; оберти ротора газогенератора; алгоритм масштабованого спряженого градієнта; вертольот; helicopter; аппроксимация нейронной сети; турбовальные двигатели вертолета